Integrativesubtractive proteomics, immunoinformatics, docking, and simulation approaches reveal candidate vaccine against Sin Nombre orthohantavirus - Alabbas, Alhumaidi B. (Frontiers in Immunology, 2022)
The emergence of Sin Nombre Orthohantavirus, an etiological agent of hantavirus cardiopulmonary syndrome, exacerbates the situation and imposes a heavy financial burden on healthcare organizations. Multi-drug resistant forms of the disease are prevalent, and there is currently no licensed commercial vaccine. Due to the numerous limitations of experimental vaccines, vaccines against various bacterial and viral diseases have developed via computational vaccine design. Several subtractive proteomics, immunoinformatics, docking, and simulation approaches were used in this study to develop a multi-epitope-based vaccine against Sin Nombre Orthohantavirus. One possible antigenic protein—the glycoprotein precursor (GPC) of surface glycoproteins accession number >AAC42202.1—was selected as a candidate for B cell derived T cell epitopes mapping after the detailed analysis of the core genome. Among the predicted epitopes, four epitopes (QVDWTKKSST, GLAASPPHL, SSYSYRRKLV, and MESGWSDTA), which were probably antigenic, non-allergenic, non-toxic, and water-soluble, were used in the multi-epitope vaccine construct. The shortlisted epitopes have the potency to cover 99.78% world population, 97.93% chines population, and 97.36% Indian population. The epitopes were connected through AAY linkers and joined with >50S Ribosomal adjuvant to enhance the efficacy. The vaccine construct comprises 182 amino acids with a molecular weight of 19.03770kDa and an instability index (II) of 26.52, indicating that the protein is stable. A molecular docking study revealed that the vaccine construct has a good binding affinity with TLR-4 and TLR-8, which is vital for immune system inducing. Top-1 docked complexes of Vaccine- TLR-4 and TLR-8 with the lowest binding energy of -12.52 kc/mol and -5.42 kc/mol respectively were considered for molecular dynamic simulation analysis. Furthermore, we predicted that the docked complexes are properly stable throughout simulation time in both normal mode and AMBER-based simulation analysis. The MMGBSA analysis calculated -122.17 and -125.4 net binding energies for TLR-8-Vaccine complex and TLR4-Vaccine complex, respectively, while the MMPBSA analysis estimated -115.63 and -118.19 for TLR-8-Vaccine complex and TLR4-Vaccine complex respectively, confirming that the binding stability with receptors is stable, which is important for inducing a strong response. However, the current work is computational based, so experimental validation is highly recommended.